DIFFERENCES IN THE PSYCHOSOCIAL STATUSES OF TREATED AND NON-TREATED ADOLESCENTS WITH ORTHODONTIC TREATMENT - Kusma Syafira Isnaini; Galuh Dwinta Sari; Diana Wibowo (FKG Unlam, 2022)
Background: Psychosocial is defined as a condition that occurs in individuals that can be seen from their behavior and influenced by the emotional development, personality, and individual social relationship. One of the factors that can affect psychosocial is the state of the teeth. The condition of misalignment teeth can have a psychosocial impact, especially adolescents. A person who has misalignment teeth should have orthodontic treatment. Orthodontic treatment can improve his psychosocial health condition. Purpose: The purpose of this study was to analyze differences in the psychosocial status of adolescents who did and did not undergo orthodontic treatment. Method: This study used an observational analytic method with a cross sectional approach. The sample size was calculated using the Slovin formula. The study was conducted at SMAN 2 Banjarmasin with a total sample of 93 students consisting of 27 students who did orthodontic treatment and 66 students who did not undergo orthodontic treatment. Data collection using a preliminary survey and PIDAQ questionnaire. Data analysis consisted of univariate analysis to describe the characteristics of each variable and bivariate analysis to see the difference between in the mean of the two groups of subjects using the Independent T Test. Results: The psychosocial status of adolescents who did orthodontic treatment is moderate with an average PIDAQ score is 50.6. The psychosocial status of adolescents who did not undergo orthodontic treatment is moderate with an average PIDAQ score is 45.8. Conclusion: There is no difference in psychosocial status between adolescents who did and did not undergo orthodontic treatment.